Applicability Of Copeptin As A Biomarker For Heart Failure - MANISHA NAITHANI; KSHITISH KUMAR KSHITIZ (International Journal of Pharma and Bio Sciences, 2011)
Heart failure is an epidemic of vast proportions accounting for the increasing hospitalizations, mortality and increasing health care costs especially in population above 65 years of age. Diagnosis of heart failure also poses a problem in women, elderly and obese, therefore the need of biomarkers. Brain Natriuretic peptides and its more stable amino-terminal co-metabolite, N Terminal – pro BNP are markers which are Food and Drug Administration (FDA) approved. Considering the limitations of these, the quest for a perfect marker continues. Some like copeptin, which have shown promise, have been a hub of much debate and interest. In the past 5 years, since the development of copeptin assay, it has been studied as a diagnostic and prognostic marker in different diseases. In the present paper we will focus our discussion on the utility of testing copeptin in heart failure to assess their clinical role and validation of its use.